Denotation-Flexibility Nature and Mobility of Dramatic Functions of Costume in “Thunderbolt: Magun” - Odule, Adesimbo Oluwakemi (NIU Journal of Humanities, 2023)
Over the years the basic nature and functions of costume had been identified and known as any material wore by the actor/character to cover his/her body or part of the body actor on stage or on screen.  Even though costume is not just about clothing the performer; it is the process of studying who and what the character in the scripts is.  In this study attempt is made to demonstrate three secondary functions of costumes serving as props, costume serving as a component of the sitting and costumes playing other causality roles in the plot of a narrative with practical samples/analyses of selected shots from a Yoruba narrative film: “Thunderbolt: Magun”. In carrying out its tasks, the paper used the research approaches of content and studio analytical methods while the theoretical yardsticks are based on David Bordwell and Kristin Thompson’s Neoformalist theory and Keir Elam’s transformability or mobility of the sign on stage structuralist principle.  With the conceptual frameworks the notions of costume and props are established.  With practical demonstration, the findings revealed not only the basic functions of costumes in each selected shots from “Thunderbolt: Magun” but went ahead to analyse samples with denotation-flexibility nature and mobility of dramatic functions of costume in serving as props, components of the sitting and playing other causality roles in “Thunderbolt: Magun”.